Tick-borne Encephalitis in the Yaroslavl Region in the Context of Planned Vaccine Prevention - T. A. Druzhinina; N. Yu. Shirina (Эпидемиология и вакцинопрофилактика)
Relevance. In the Yaroslavl region, the Central Federal District of Russia, endemic for tick-borne encephalitis (TBE), specific TBE vaccination has been routinely carried out for more than 20 years. Therefore, the evaluation of the results of long-term universal immunoprophylaxis the population has a practical and scientific interest. Purpose: To study the epidemiology of tick-borne encephalitis in the context universal vaccine in 2008-2019. Results and discussion. According to the results of long-term immunization, by 2019 19.1% of the population was vaccinated, while vaccine coverage for the children living in endemic areas of the region reaches 68-83%. The article noted a 2.9-fold decrease in the incidence of TBE in 2013-2018 compared with 2008-2012. The average long-term level was 0.69 per 100 ths people. TBE was recorded among the unvaccinated population, mild febrile forms prevailed - 56.8%, however, the proportion of focal forms of the disease remained high (36.3%). Deaths from TBE in the period from 2013-2018 did not have. Thus, in the absence of specific treatment for TBE, vaccine prophylaxis is of great medical and social importance for the Yaroslavl region endemic for TBE. Conclusion. Vaccine coverage in the population of Yaroslavl region, children living in endemic areas and natural immunization in natural foci of TBE contributed to the formation of a significant level of collective immunity of the population to TBE, reducing the incidence of in the last 5 years.